Precision soft tissue balancing: grid-assisted pie-crusting in total knee arthroplasty - Rezaei, Arash; Moon, John; Lichtig, Asher; Mera, Barbara; Drake, Brett; Choubey, Apurva S.; Kim, Sunjung; Tueni, Nicole; Piponov, Hristo; Koh, Jason; Karam, Joseph; Amirouche, Farid (Frontiers in Surgery, 2024)
Currently, there is a lack of consensus on optimal techniques for soft-tissue balancing to address varus and valgus deformities during total knee arthroplasty (TKA). In this manuscript, we assess the efficacy of a novel pie-crusting technique for soft-tissue balancing of the knee. More specifically, we tested progressive needle pie-crusting of the medial collateral ligament (MCL) and lateral collateral ligament (LCL) using a customized grid for addressing varus and valgus deformities of the knee, respectively. This approach can serve as a useful, algorithmic tool for orthopaedic surgeons performing TKAs.